Pronunciation Problems English Language Students Encounter at University Level and Their Effect on The Students` Performance - Warregh, Najat Ali (Sharwes Scientific Journal, 2024)
Speaking the English language has become very important nowadays because it helps communication in any place around the world and increases the chance of getting better job opportunities. Learning correct pronunciation is not less important than learning any of the other skills of the language, and students seem to have plenty of words which are wrongly pronounced at any level of learning the target language.The current study intended to explore pronunciation problems of English university students in Nalut. This study attempted to underline the most common pronunciation mistakes and the factors triggering those mistakes and how they affect students` performance. Classroom observation and follow up interviews were chosen to collect data for the study. Students were observed and recorded while reading a passage, and their reading mistakes were then analyzed. One of the main findings of the research revealed that English language students have a problem of not correctly articulating the sounds / q /, / dʓ /, /tʃ / and /p / and inserting a vowel sound between consonants in some words and also pronouncing the silent letters. Finally, students show difficulties related to pronouncing vowels and diphthongs. These problems seemed to affect their speaking significantly